Studies on the Deviation of a Solution from the Hypothetical Ideal Solution with the Total Activity Coefficient - Yeqiu Zhou; Feiwu Chen; Yu Zhou (Molecules)
The total activity coefficient is exploited to study the deviation of a solution from the hypothetical ideal solution. It is proven for a solution that the curve of the total activity coefficient and all curves of activity coefficients of components will intersect at the stationary point of the total activity coefficient curve. It is found for the negative (positive) deviation binary solutions studied here that the magnitudes of the total activity coefficient at the minimum (maximum) point of the total activity coefficient curve becomes bigger as the intermolecular attraction of the solute and solvent become weaker. Furthermore, the shape of the total activity coefficient curve, as well as the molar concentration of its stationary point, are dependent on the intermolecular attraction of components in the solution. Finally, for the negative solution of tetrahydrofuran + 1,1,2,2-tetrachloroethane and the positive-deviation solution of ethyl isobutyrate + 1-butanol, the effects of pressure on the total activity coefficient of the negative and positive solutions are investigated.